Porous Chitosan/Hydroxyapatite Composite Microspheres for Vancomycin Loading and Releasing - Meng-Ying Wu; Yi-Ting Kuo; I-Fang Kao; Shiow-Kang Yen (MDPI AG, 2024)
Porous chitosan/hydroxyapatite (Chi-HAp) composite microspheres were prepared in an aqueous solution containing chitosan, calcium nitrate, and ammonium dihydrogen phosphate by using a hydrothermal method at various temperatures. The investigation indicated that temperature significantly impacted the final product's appearance. Hydroxyapatite (HAp) coupled with dicalcium phosphate dihydrate (DCPD) flakes were obviously found at 65 and 70 °C, while the latter gradually disappeared at higher temperatures. Conversely, synthesis at 90 °C led to smaller particle sizes due to the broken chitosan chains. The microspheres synthesized at 75 °C were selected for further analysis, revealing porous structures with specific surface areas of 36.66 m2/g, pores ranging from 3 to 100 nm, and pore volumes of 0.58 cm3/g. Vancomycin (VCM), an antibiotic, was then absorbed on and released from the microspheres derived at 75 °C, with a drug entrapment efficiency of 20% and a release duration exceeding 20 days. The bacteriostatic activity of the VCM/composite microspheres against Staphylococcus aureus increased with the VCM concentration and immersion time, revealing a stable inhibition zone diameter of approximately 4.3 mm from 24 to 96 h, and this indicated the retained stability and efficacy of the VCM during the encapsulating process.